INFLUENCE OF MONSOON TRANSITION ON THE ANNUAL CYCLE OF RAINFALL IN JAVA ISLAND - AGUNG FAUZI (NIM : 12812602); Pembimbing : Dr. Tri Wahyu Hadi, M.Sc, MUHAMMAD
The rainfall pattern over Java Island had been assumed to be of monsoonal type with one maximum value in the December-January-February (DJF) period. However, monthly rainfall data from some stations in the southern part of Java Island tend to show second maximum value during the March-April-May (MAM) of monsoon transition period. The influence of the monsoon transition on the rainfall of Java Island has been further investigated by analyzing data from Tropical Rainfall Measuring Mission (TRMM) satellite, Cross-Calibrated Multi-Platform (CCMP), and Multi-functional Transport SATellite-InfraRed 1 (MTSAT-IR1), as well as local rainfall observations. Signals with annual and semi-annual cycles were extracted from the monthly rainfall data using Fast Fourier Transfrom (FFT) method. The ratio between the amplitudes of semi-annual and the annual cycles was then calculated and plotted on the map to delineate regions that have second rainfall maximum during MAM. The results show that three regions around Bandung, Kebumen, and Trenggalek can be identified as the areas that are most influenced by the MAM monsoon transition. Results of further analysis of MTSAT-IR1 and CCMP wind data indicate that the convective activities were concentrated in those regions due to the interaction between the low-level wind and the complex topography of Java Island. The topography seems to play role in blocking the southerly component of the monsoon flows so that convective activities in the south tend to be stronger compared to that in the northern part of Java Island. These results confirm that rainfall maximum in Java Island cannot be uniformly defined during the DJF period because some areas may also have rainfall maximum during the MAM monsoon transition.